2007
DOI: 10.1073/pnas.0709915104
|View full text |Cite
|
Sign up to set email alerts
|

Localizing frustration in native proteins and protein assemblies

Abstract: We propose a method of quantifying the degree of frustration manifested by spatially local interactions in protein biomolecules. This method of localization smoothly generalizes the global criterion for an energy landscape to be funneled to the native state, which is in keeping with the principle of minimal frustration. A survey of the structural database shows that natural proteins are multiply connected by a web of local interactions that are individually minimally frustrated. In contrast, highly frustrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
451
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 322 publications
(473 citation statements)
references
References 32 publications
22
451
0
Order By: Relevance
“…It is now textbook knowledge (Williamson, 2012) that proteins are dynamic and that structural states should be treated as ensembles that fluctuate around energy minima. This behavior is described by the energy landscape theory (Frauenfelder et al 1991), which can be applied to protein dynamics using the principle of minimal frustration (Ferreiro et al 2007(Ferreiro et al , 2014Jenik et al 2012). NMR spectroscopy has developed in parallel with the energy landscape theory, and the two research fields are now converging to provide an unprecedented understanding of protein function.…”
Section: Introductionmentioning
confidence: 99%
“…It is now textbook knowledge (Williamson, 2012) that proteins are dynamic and that structural states should be treated as ensembles that fluctuate around energy minima. This behavior is described by the energy landscape theory (Frauenfelder et al 1991), which can be applied to protein dynamics using the principle of minimal frustration (Ferreiro et al 2007(Ferreiro et al , 2014Jenik et al 2012). NMR spectroscopy has developed in parallel with the energy landscape theory, and the two research fields are now converging to provide an unprecedented understanding of protein function.…”
Section: Introductionmentioning
confidence: 99%
“…The standard deviation was 6.38 for trans peptide bonds with about 12% and 0.5% of residues deviating more than 108and 208, respectively, from planarity. As not all parts of a crystal structure have the same level of reliability, we examined the electron density of every peptide with x 208 from planar to assess which were reliable; then using the reliable examples, we showed that these highly nonplanar peptides are not just in active sites, but represent a mundane aspect of protein structure that simply reflects the "frustration" [16][17][18] that occurs as proteins fold into their tertiary structures. We (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…An idealised conformational selection mechanism would require that it be more likely for the proteins to dissociate before any transition to the bound conformation could occur. 24 This would have presumably been the case if there were a greater degree of "frustration" 76 between the NCBD-like contacts to ACTR, and the contacts stabilizing protein G.…”
Section: B Binding Transition Pathsmentioning
confidence: 99%